The importance of organisational culture for health system resilience: A qualitative analysis of factors that supported health care workers in Germany during the COVID-19 pandemic - Heide Weishaar; Megan Evans; Souaad Chemali; Eloisa Montt Maray; Rike Böttcher; René Umlauf; Susan Abunijela; Nadine Muller; Barbara Buchberger; Brogan Geurts; Hanna-Tina Fischer; Charbel El Bcheraoui (PLoS ONE, 2025)
Health system resilience is defined as the ability of a system to prepare, manage, and learn from shocks. This study investigates the resilience of the German health system by analysing the system-related factors that supported health care workers, a key building block of the system, during the COVID-19 pandemic. We thematically analysed data from 18 semi-structured interviews with key informants from management, policy and academia, 17 in-depth interviews with health care workers, and 10 focus group discussions with health care workers. We identified six categories of factors which supported health care workers during the pandemic: (1) appreciation and encouragement; (2) team support and communication; (3) collaboration across professions and institutions; (4) informational, material and technical support; (5) leadership and participation; and (6) creativity and innovation. The analysis highlights the importance of systemic and organisational factors for maintaining health system resilience. The need to improvise and develop pragmatic solutions to deal with COVID-related challenges offered ample opportunities for participation, self-determination, innovation, and alternative work processes. Learning from adaptations made during the pandemic and implementing sustainable organisational and systemic changes to increase participation, conducive organisational cultures, and non-hierarchical working styles hold promising potential for health system transformation and health system strengthening.